2020
DOI: 10.1155/2020/3957193
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment of Non‐Small‐Cell Lung Cancer Using Shenyi Capsule and Platinum‐Based Chemotherapy: A Meta‐Analysis and Systematic Review

Abstract: Background.The efficacy and safety of combined treatment of non-small-cell lung cancer (NSCLC) using Shenyi capsules and platinum-based chemotherapy were comprehensively evaluated. Methods. A computer-based search was used to identify reports on clinical randomized controlled trials (RCTs) on this combined treatment for NSCLC from the PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), VIP, China Biomedical (CBM), and Wanfang Data electronic databases. The databases were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Of which the principal component is Rg 3 , Shenyi Capsule produced by our company (Jilin Yatai Pharmaceutical Co., Ltd.) has been applied as an adjuvant to conventional cancer therapies in China. 9,10 In addition to its anti-cancer activity, the cardiovascular protective effects of Rg 3 have also been shown by our group and others in a variety of animal disease models, including myocardial infarction, 11 hypertension, 12 and atherosclerosis. 13 Along this line, we found that Rg 3 improves hypertensive nephropathy in rats and mice with hypertension.…”
mentioning
confidence: 73%
“…Of which the principal component is Rg 3 , Shenyi Capsule produced by our company (Jilin Yatai Pharmaceutical Co., Ltd.) has been applied as an adjuvant to conventional cancer therapies in China. 9,10 In addition to its anti-cancer activity, the cardiovascular protective effects of Rg 3 have also been shown by our group and others in a variety of animal disease models, including myocardial infarction, 11 hypertension, 12 and atherosclerosis. 13 Along this line, we found that Rg 3 improves hypertensive nephropathy in rats and mice with hypertension.…”
mentioning
confidence: 73%
“…Adverse reactions were classified according to the toxicity classification standards of the WHO and divided into grades 0–IV. Grade II–IV toxicities were considered adverse reactions [ 19 ]. Secondary outcome indices of efficacy were leukocyte and platelet toxicities, as well as vomiting in the digestive tract.…”
Section: Methodsmentioning
confidence: 99%
“…e first meta-analysis of chemotherapy and optimal supportive treatment for advanced NSCLC published in the Journal of Clinical Oncology (2008) has confirmed that supportive treatment combined with chemotherapy can improve the survival rate of advanced NSCLC [26,27] and has a significant effect in reducing toxic side effects [28] and chemoresistance [29] of chemotherapy. Obviously, chemotherapy has a direct cytotoxic effect on NSCLC [30][31][32], while Shenyi capsule synergically increases the efficacy of chemotherapy by reducing toxicity, increasing sensitization, enhancing immunity, etc.…”
Section: Yin-yang Balance Effect Of Shenyi Capsulementioning
confidence: 99%
“…Because there is no single mechanism that can explain the nature of toxic side effects and chemoresistance, the combination therapy based on different mechanisms cannot really get rid of them. Aiming at the abovementioned defects of chemotherapy, the combination of Shenyi capsule mainly improves severe acute vomiting above Grade II [27] and effectively improves hemocytotoxicity and platelet inhibition caused by chemotherapy [27]. Due to the "vascular inhibition effect" of Shenyi capsule [38], the "vascular network" that tumors depend on for survival is blocked, and the rapid proliferation of tumor during the intermittent period of chemotherapeutics is also blocked, which effectively consolidates the phased curative effect achieved by chemotherapy.…”
Section: Toxic Side Effects and Chemoresistance Of Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation